2004
DOI: 10.1385/nmm:5:3:243
|View full text |Cite
|
Sign up to set email alerts
|

Association Analysis of the Dopamine D3 Receptor Gene ser9gly and Brain-Derived Neurotrophic Factor Gene val66met Polymorphisms With Antipsychotic-Induced Persistent Tardive Dyskinesia and Clinical Expression in Chinese Schizophrenic Patients

Abstract: The association between the dopamine D3 receptor (DRD3) ser9gly genetic polymorphism and tardive dyskinesia (TD), a serious adverse motor disorder after long-term antipsychotic treatment, has been studied extensively in recent years. However, the existence of inconsistent reports makes the role of the DRD3 ser9gly polymorphism in TD development questionable. In rodent studies, the DRD3 expression could be controlled by the brain-derived neurotrophic factor (BDNF), a member of the neurotrophin family. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 41 publications
0
34
0
3
Order By: Relevance
“…However, the modest ORs also suggest further contribution of other genes in the development of this severe side effect. In a somewhat surprising result, Liou et al 203 found no association between the D3 Ser9Gly polymorphism and TD in 216 Chinese schizophrenic patients (uncorrected for age), but reported association with heterozygosity for a BDNF Val66Met polymorphism. Srivastava et al 204 also failed to find association between D3 polymorphism and TD, but reported association between COMT, the enzyme that controls dopamine turnover, and TD, a finding not confirmed by other independent studies.…”
Section: Prediction Of Side Effectsmentioning
confidence: 95%
“…However, the modest ORs also suggest further contribution of other genes in the development of this severe side effect. In a somewhat surprising result, Liou et al 203 found no association between the D3 Ser9Gly polymorphism and TD in 216 Chinese schizophrenic patients (uncorrected for age), but reported association with heterozygosity for a BDNF Val66Met polymorphism. Srivastava et al 204 also failed to find association between D3 polymorphism and TD, but reported association between COMT, the enzyme that controls dopamine turnover, and TD, a finding not confirmed by other independent studies.…”
Section: Prediction Of Side Effectsmentioning
confidence: 95%
“…The super family of GPCRs contribute in many psychiatric and neuropsychiatric illnesses (28,29). Among the GPCRs, the eminent role of DRD3 in etiology and therapeutic response of many of these disorders has been frequently reported (8,(30)(31)(32). However, except a few studies (8,33) not much has been conveyed regarding autism.…”
Section: Discussionmentioning
confidence: 99%
“…Existen varios genes candidatos (COMT, CYP1A2, CYP3A4, D2, D3, 5-HT2A, 5-HT2C, …), que se han localizado como posibles responsables, si bien no hay ningún estudio totalmente concluyente al respecto 145,146,147 .…”
Section:  Discinesia Tardíaunclassified